Becoming a Paralympic champion—analysis of the morpho-functional abilities of a disabled female athlete in cross-country skiing over a 10-year period - Gawronski, W. (International Journal of Environmental Research and Public Health, 2023)
Changing medical classification into the functional one in disabled cross-country skiing means that the athlete`s predispositions and performance abilities most of all determine the final result in cross-country skiing. Thus, exercise tests have become an indispensable element of the training process. The subject of this study is to present a rare analysis of morpho-functional abilities in relation to the implementation of training workloads during the training preparation for a Paralympic champion in cross-country skiing when she was close to her maximal achievements. The study was performed to investigate abilities evaluated during laboratory tests and how they relate to performance outcomes during major tournaments. An exercise test to exhaustion on a cycle ergometer was performed three times a year on a cross-country disabled female skier over a 10-year period. The morpho-functional level which enabled the athlete to compete for gold medals in the Paralympic Games (PG) is best reflected in the results obtained by her in the tests in the period of direct preparation for the PG and confirms optimal training workloads in this time. The study showed, that the VO2max level is presently the most important determinant of physical performance achieved by the examined athlete with physical disabilities. The aim of this paper is to present the level of exercise capacity of the Paralympic champion based on the analysis of the results of the tests in relation to the implementation of training workloads.